Anti-inflammatory properties of an A3 adenosine receptor agonist, piclidenoson, in a model of human peripheral blood mononuclear cell culture - Kozić, Ljiljana; Mališ, Vanja; Drakul, Marija; Rakočević, Sara; Bokonjić, Dejan; Mihajlović, Dušan (Vojnosanitetski pregled, 2025)
Background/Aim. Piclidenoson (CF101, IB-MECA), a selective agonist of the A3 adenosine receptor (A3AR), is used in clinical trials for the treatment of psoriasis. Emerging data from in vitro and in vivo studies suggest that piclidenoson possesses anti-inflammatory and immunomodulatory properties, but its action on human peripheral blood mononuclear cells (PBMCs) remains unknown. The aim of this study was to examine the anti-inflammatory effects of piclidenoson in a model of phytohaemagglutinin (PHA)-stimulated human PBMCs culture. Methods. Human PBMCs were isolated from the venous blood of healthy donors (n = 4) and treated with different concentrations of piclidenoson. Flow cytometry and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test were used to determine cell viability, while the MTT method and the carboxyfluorescein succinimidyl ester (CFSE) staining method were used to analyze the effect of piclidenoson on cell proliferation. Levels of tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, IL-23, IL-36, IL-5, interferon (IFN)‐γ, IL-17, and IL-10 were measured using a specific sandwich enzyme-linked immunosorbent assay (ELISA). Results. The results of cytotoxicity tests showed that the highest applied concentration of piclidenoson (1,500 nM) reduced the metabolic activity of PBMCs (p < 0.05) and increased the percentage of late apoptotic (p < 0.05) and necrotic cells (p < 0.01). Non-toxic concentrations (250, 500, and 1,000 nM) decreased the proliferation of PBMCs (p < 0.05) compared to the control cells. These concentrations also decreased the production of TNF-α (p < 0.001). Piclidenoson at concentrations of 250 and 1,000 nM reduced the production of IL-23 (p < 0.05) while the concentrations of 500 and 1,000 nM reduced the production of IL-36 (p < 0.05). Piclidenoson at 1,000 nM increased IL-1β production, while other concentrations decreased its production (p < 0.01). The highest concentration (1,000 nM) inhibited the production of IL-5 (p < 0.05) and IFN-γ (p < 0.01) while all applied concentrations inhibited the production of IL-17 (p < 0.001). Furthermore, piclidenoson increased the production of IL-10 in all applied concentrations (p < 0.01). Conclusion. At non-toxic concentrations, piclidenoson exerts anti-inflammatory properties associated with the inhibition of proliferation and modulation of cytokine production in PHA-stimulated PBMCs culture.